Effects of source digital elevation models in assessment of gross runoff-river hydropower potential: A case study of West Rapti Basin, Nepal - Bista, Sunil; Singh, Umesh; Kayastha, Nagendra; Ghimire, Bhola NS; Talchabhadel, Rocky (Journal of Engineering Issues and Solutions, 2021)
Advancements in Geographical Information System (GIS), Remote Sensing (RS) technology, hydrologic modeling and availability of wider coverage hydrometeorological data have facilitated the use of GIS and hydrological modelling tools in studies related to hydropower potential. Digital Elevation Model (DEM) is the primary data required for these tools. They have become more accessible and many are freely available. These DEMs have different resolution and their errors vary due to their primary data acquisition techniques and processing methods. However, their effects on the hydropower potential assessment are less investigated. This study evaluates the effects of 6 freely available DEMs: ALOS 12.5 m, SRTM 90 m, SRTM 30 m, ASTER G-DEM version-3 30 m, AW3D 30 m and Cartosat-1 version-3 30 m on the Gross Run-off-River Hydropower Potential (GRHP) assessment, using GIS and hydrological modelling tools. West Rapti River (WRR) basin in Nepal was chosen for the case study. Soil and Water Tool (SWAT) hydrological model, coupled with GIS was used to discretize the WRR basin into several sub-basins/streams. Flow at the inlet and outlet of streams were estimated from the SWAT model whereas the topographic head was extracted from the DEMs. The GRHP of the streams were computed using the estimated stream flow and the topographic head for flows at 40% to 60% Probability of Exceedance (PoE). The total potential of the basin was computed by summing up the potential of all streams. The GRHP of WRR basin for flows at 40% PoE was estimated as 512 MW for ALOS 12.5 m resolution DEM, referred as a base case in this study. The GRHP estimated from the remaining DEMs showed the variation of less than 6% compared to the base case. The topographic head was found to be sensitive with respect to the DEM resolution and the highest variations were observed in the main river channels.